Plasma and Thermal Spraying - Ružbarský, Juraj; Panda, Anton (SpringerBriefs in Applied Sciences and Technology, 2017)
This book presents the principles of plasma and heat spraying. It introduces plasma jet and the formation of plasma sprayed coatings. It explains the adhesion process and also presents standard methods for measurement according to DIN forms. Some case studies are presented for illustration.